A new report on the parasitisation of Epitranus Walker (Chalcidoidea: Chalcididae) on Phereoeca uterella (Walsingham) (Lepidoptera: Tineidae) with the description of a new species from India. (2nd October 2021) - Binoy, Chereekandy; Shreevihar, Santhosh; Nasser, Mannankadiyan; Jyolsna, Kattumunda
ABSTRACT: Epitranus Walker, the only representative genus of the Subfamily Epitraninae (Hymenoptera: Chalcididae) is represented by 68 species worldwide. Host record of the genus is limited to a few species parasitising crambid, pyralid and tineid moths with very little definitive records. A new species Epitranus uterellophagus Binoy & Santhosh, sp. nov . parasitising pupae of Phereoeca uterella (Walsingham, 1897) (Lepidoptera: Tineidae) is described with illustrations from India. http://www.zoobank.org/urn:lsid:zoobank.org:act:01040126-83A9-4253-B0F9-08EA2D89EC25